Calculation of genetic risks in Duchenne muscular dystrophy by geneticists in the United Kingdom. - Bundey, S (1978)
Pedigrees of Duchenne muscular dystrophy were sent to 32 geneticists in the United Kingdom, asking for their calculations for genetic risks for female relatives. Eighteen participated, of whom only 7 gave correct answers for all pedigrees. The method most used for calculations (the 'Bayesian' method) was most liable to errors in new situations. An alternative, simpler method is presented.